Macular teleangiectasia – a diagnostic and therapeutic challenge - Kozicka, Katarzyna; Karska-Basta, Izabella; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Macular telangiectasia denotes a group of diseases of unclear cause which involve changes to retinal blood vessels. Based on ophthalmoscopy, fluorescein angiography and optical coherence tomography findings, we can distinguish type 1 and type 2 macular teleangiectasia. Type 1 is usually a unilateral dilatation of vessels in the parafoveal region with microaneurysms. It typically affects young males with macular oedema causing visual loss. The course is mild, and the prognosis is good. Type 2 affects men and women equally. It is characterised by abnormalities in perimacular blood vessels, which cause hyperplasia of retinal pigment epithelium. It is bilateral and vision loss is caused by the loss of Müller cells. The prognosis is poor. Treatment of macular teleangiectasia depends on its type. In type 1, the most common treatment is laser photocoagulation of leakage areas within the retina. In type 2, as a neurodegenerative process, there is no effective treatment so far.